Development of In Vitro Maturation for Human Oocytes Natural and Mild Approaches to Clinical Infertility Treatment - Chian, Ri-Cheng.; Nargund, Geeta; Huang, Jack Y. J.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
An ideal reference for infertility specialists and reproductive endocrinologists alike, this comprehensive text discusses current natural and mild approaches to in vitro fertilization (IVF) and the development of in vitro maturation (IVM) as a clinical treatment. It is divided thematically into four sections. Part I presents the basic science of ovarian endocrinology and the mechanism of oocyte maturation, including follicular development and the importance of mitochondrial changes. The differences between natural cycle IVF and stimulated IVF are presented in part II, including the standard ovarian stimulation protocols and their outcomes and the etiology, prevention and management of ovarian hyperstimulation syndrome (OHSS). Minimal and mild stimulation for IVF is discussed in part III, including mild stimulation protocols for oncofertility patients and the new minimally invasive INVO procedure. In vitro maturation as a clinical treatment is the subject of part IV, discussing the methodology of immature oocyte retrieval as well as other laboratory aspects and congenital and obstetrical outcomes of babies born from IVM. Combining expertise from thought leaders around the world, Development of In Vitro Maturation for Human Oocytes will be a go-to resource for infertility researchers and practitioners and reproductive endocrinologists working with infertile couples looking for safer and more cost-effective options for treatment.
Part I: Ovarian Function -- Ovarian Endocrinology -- Follicular Development and Oocyte Growth -- A New Understanding of the Regulation of Oocyte Meiotic Prophase Arrest and Resumption -- Mitochondria of the Oocyte -- Part II: Natural Cycle IVF and Stimulation Cycle IVF -- Natural Cycle IVF: Summary of the Current Literature -- Follicular Fluid Hormone Profiles in Natural Cycle IVF Patients during Follicular Phase -- Standard Ovarian Stimulation Protocols and Their Outcomes -- Which Women Are Suitable for Natural and Modified Natural Cycle IVF? -- Natural Cycle IVF with Spontaneous LH Surge -- Etiologies and Risk Factors of Ovarian Hyperstimulation Syndrome -- Prevention and Management of Ovarian Hyperstimulation Syndrome -- Part III: Minimal or Mild Stimulation for IVF -- Cumulative Pregnancy Rates after Six Cycles of Modified Natural Cycle IVF -- Minimal Stimulation for IVF with Clomiphene Citrate -- Mild Stimulation Protocols: Combination of Clomiphene Citrate and Recombinant FSH or HMG -- Mild Stimulation Protocol for Poor Ovarian Responders Undergoing IVF -- The Application of Natural Cycle IVF in Primary Ovarian Insufficiency -- Mild Stimulation Protocols for Oncofertility Patients -- Minimally Invasive IVF as an Alternative Treatment Option for Infertile Couples: (INVO) Procedure -- Accessible Infertility Care: From Dream to Reality -- Genetic Aspects of Recurrent Implantation Failure -- Part IV: Development of In Vitro Maturation -- IVM as Clinical Treatment: Overview -- Avoidance of Severe Ovarian Hyperstimulation with IVM Treatment -- Immature Oocyte Retrieval for IVM Treatment -- Laboratory Aspect of IVM Treatment -- Obstetric Outcomes of In Vitro Maturation Treatment and Risk of Congenital Malformations -- Development of IVM Treatment: Combination of Natural Cycle IVF with IVM.
Keywords: Medicine; Endocrinology; Reproductive medicine; Medicine & Public Health; Reproductive medicine; Endocrinology